Teachers' issues: A case for mental health [PowerPoint presentation] - Reece-Peters, Cecilia (My University, 2013)
Mental health has been described as "a state of well-being in which an individual realizes his or her own abilities, can cope with the normal stresses of life, can work productively and is able to make a contribution to his or her community." In this positive sense, mental health is the foundation for individual well-being and the effective functioning of a community (WHO, 2010). Despite the fact that the concept of mental health takes everyone into consideration, within the context of schooling in the Caribbean, there seems to be a perception that any attempt at mental health interventions should be exclusively for the student population. Counselling programmes at primary schools, for example, target students while members of staff are given little or no consideration. This paper presents the findings and analysis of the mental health issues identified by two cohorts of third-year in-service primary school teachers. in Trinidad and Tobago. The issues described by the teachers are considered as "mental health symptoms." Recommendations are made for Caribbean primary school health interventions to develop and implement an assessment and management approach to teachers' mental health
Paper presented at the Biennial Conference of The University of the West Indies Schools of Education, 23-25 April, 2013, St. Augustine, Trinidad and Tobago
Keywords: Primary school teachers; Mental health; Student teachers; Conference papers; Trinidad and Tobago